AI as your ally: The effects of AI‐assisted venting on negative affect and perceived social support - Hu, Meilan; Chua, Xavier Cheng Wee; Diong, Shu Fen; Kasturiratna, K. T. A. Sandeeshwara; Majeed, Nadyanna M.; Hartanto, Andree (Applied psychology : health and well-being, 2025)
In recent years, artificial intelligence (AI) chatbots have made significant strides in generating human‐like conversations. With AI's expanding capabilities in mimicking human interactions, its affordability and accessibility underscore the potential of AI chatbots to facilitate negative emotional disclosure or venting. The study's primary objective is to highlight the potential benefits of AI‐assisted venting by comparing its effectiveness to venting through a traditional journaling platform in reducing negative affect and increasing perceived social support. We conducted a pre‐registered within‐subject experiment involving 150 participants who completed both traditional venting and AI‐assisted venting conditions with counterbalancing and a wash‐out period of 1‐week between the conditions. Results from the frequentist and Bayesian dependent samples t‐test revealed that AI‐assisted venting effectively reduced high and medium arousal negative affect such as anger, frustration and fear. However, participants in the AI‐assisted venting condition did not experience a significant increase in perceived social support and perceived loneliness, suggesting that participants did not perceive the effective assistance from AI as social support. This study demonstrates the promising role of AI in improving individuals' emotional well‐being, serving as a catalyst for a broader discussion on the evolving role of AI and its potential psychological implications.